INVESTIGATION OF EARLY PERMANENT TOOTH LOSS IN PATIENTS BETWEEN 10-25 YEARS OF AGE IN ELAZIĞ REGION - Şen, Yakup; Baybars, Sümeyye Coşgun; Ok, Elif (Harran Üniversitesi, 2023)
Objective: To determine the prevalence and distribution of permanent missing teeth accor-ding to gender and location, to investigate the causes of early tooth loss and to emphasize the importance of early diagnosis. Material and method: Panoramic radiographs of 1879 patients (1037 women, 842 men) aged between 10-25 years who applied to Fırat University Faculty of Dentistry were evalua-ted retrospectively. A standardized research form was used in the study. The patients were evaluated in terms of gender, location and number of missing teeth. The obtained data were anaylzed statistically by chi-square and one-sided chi-square tests. Results: In the total of 1879 panoramic radiographs, 569 missing permanent teeth were identified in 299 patients (175 women, 124 men). The prevalence of permanent missing te-eth was found to be 15.9% (16.9% female, 14.7% male). The most commonly missing teeth were determined as: lower first molar, lower second premolar and upper lateral incisor, res-pectively. Permanent tooth loss was more common in the mandibula than in the maxilla and a statistically significant difference was obtained. Among patients with missing teeth, the prevalance of patients with only one missing tooth was found to be 48.2%. Conclusion: Detailed radiological and clinical examination is the key in the diagnosis of missing teeth and early diagnosis is of great importance for treatment planning. Keywords: Hypodontia; Congenital missing teeth; Permanent missing teeth

Amaç: Daimi diş eksikliğinin cinsiyete ve lokalizasyona göre prevalansını ve dağılımını tespit etmek, erken diş kayıplarının nedenlerini araştırmak ve erken teşhisin önemini vurgu-lamaktır. Materyal ve metot: Fırat Üniversitesi Diş Hekimliği Fakültesi’ne başvuran 10-25 yaş arası 1879 (1037 kadın, 842 erkek) hastaya ait panoramik radyografiler retrospektif olarak değer-lendirildi. Çalışmada standardize bir araştırma formu kullanıldı. Hastalar cinsiyet, diş eksik-liğinin lokalizasyonu ve sayısı yönünden incelendi. Elde edilen veriler istatistiksel olarak ki kare ve tek gözlü düzende ki-kare testi ile değerlendirildi. Bulgular: Toplam 1879 panoramik radyografide, 299 hastada (175 kadın, 124 erkek) 569 adet daimi diş eksikliği belirlendi. Daimi diş eksikliği prevelansı %15.9 (% 16.9 kadın, %14.7 erkek) olarak bulundu. Eksikliği en sık görülen dişler sırasıyla: alt birinci büyük azı, alt ikinci küçük azı ve üst yan kesici diş olarak belirlendi. Daimi diş eksikliği alt çenede üst çeneye oranla daha fazla görülüp istatistiksel olarak anlamlı fark elde edildi. Diş eksikliği görülen hastalar içerisinde sadece bir dişi eksik hasta oranı %48.2 bulundu. Sonuç: Diş eksiklerinin teşhisinde detaylı radyolojik ve klinik muayene anahtar rolündedir ve erken teşhis tedavi planlaması açısından büyük önem taşır. Anahtar Kelimeler: Hipodonti; Konjenital diş eksikliği; Daimi diş eksikliği
ELAZIĞ YÖRESİNDE 10-25 YAŞ ARALIĞINDAKİ HASTALARDA DAİMİ DİŞLERİN ERKEN KAYIPLARININ İNCELENMESİ
Keywords: Oral and Maxillofacial Radiology; Ağız; Diş ve Çene Radyolojisi; Paedodontics; Çocuk Diş Hekimliği